DIVERSIDADE LINGUÍSTICA NA COLÔNIA MENONITA WITMARSUM : UMA ANÁLISE DA PAISAGEM LINGUÍSTICA LOCAL - ANDRADE, JANAINA PALHANO (2022)
The present research aims to describe and analyze the Linguistic Landscape of the Witmarsum Colony, located in the municipality of Palmeira (PR). Founded by a group of German Mennonite immigrants, it is linguistically constituted by the contact of three named languages: the Plautdietsch; the Hochdeutsch; and the Portuguese - besides its varieties -. Despite our country's history of linguistic homogenization, several studies and researches claim that Brazil is multilingual, due to the multiplicity of peoples that colonized it. Thus, the focus of this study is linguistic diversity in the visual spaces of the colony, focusing on issues of language policy and multilingualism. The research is field, interdisciplinary and qualitative, with an approach in Sociolinguistics and Applied Linguistics, and the corpus was collected in the local linguistic scenario through the photographic record of the official and unofficial signs of the public space; it counted on a quantitative of 80 units of analysis, considering informative signs, signs of businesses and public institutions, street signs, traffic signs, billboards, service provider signs, tombstones, menus, among others. The theoretical framework was grounded by Calvet (2007); Lagares (2018); Spolsky (2004, 2009, 2016); Landry and Bourhis (1997); Gorter (2013); Shohamy (2006, 2010); Ben-Rafael et al. (2006); Cenoz and Gorter (2008); Backhaus (2006), Blommaert (2013) etc. The results indicate the predominance of Portuguese in the official signs, while in the unofficial signs, the Hochdeutsch immigration language, along with Portuguese - bilingual signs - had greater visibility. The Plautdietsch - language of the Mennonites - had no expressiveness in the linguistic landscape, even after the implementation of the language policy of co-officialization of the language. Thus, it is understood that there is a practice of language commodification in the use of Hochdeutsch, in order to add economic value and disseminate local tourism. The Plautdiestch, in turn, has a cultural function, which represents the identity of the German Mennonite people, but its authenticity and legitimacy are camouflaged by the languages that are institutionalized by teaching and gain greater emphasis in the linguistic landscape of the public space. In this way, there is a verticalized politics, in the sense that Plautdietsch is co-official, but it is Hochdeutsch that is taught at the college. So as long as Plautdietsch is not inserted into teaching, it will not have its legitimate use and will therefore be invisible in the linguistic landscape.